RE: Risk of HBV Reactivation in HBsAg Negative and AntiHBc IgG Positive Patients Receiving Biologic Therapy - Rahmi Aslan; Özlen Atuğ; Haner Direskeneli; Tülin Ergun; Yeşim Özen Alahdab; Dilek Seçkin; Mehmet Pamir Atagündüz; Nevsun İnanç; Fatma Alibaz Öner; İlkay Ergenç; Gizem Sevik; Seda Kutluğ Ağaçkıran; et al. (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Ergenç İ, Kani HT, Karabacak M, et al. RE: risk of HBV reactivation in HBsAg negative and anti-HBc IgG positive patients receiving biologic therapy. Turk J Gastroenterol. 2023;34(3):310.